Co-transcriptional degradation of aberrant pre-mRNA by Xrn2 - Davidson, Lee (Nature Publishing Group, 2012)
Eukaryotic protein-coding genes are transcribed as pre-mRNAs that are matured by capping, splicing and cleavage and polyadenylation. Although human pre-mRNAs can be long and complex, containing multiple introns and many alternative processing sites, they are usually processed co-transcriptionally. Mistakes during nuclear mRNA maturation could lead to potentially harmful transcripts that are important to eliminate. However, the processes of human pre-mRNA degradation are not well characterised in the human nucleus. We have studied how aberrantly processed pre-mRNAs are degraded and find a role for the 5′→3′ exonuclease, Xrn2. Xrn2 associates with and co-transcriptionally degrades nascent β-globin transcripts, mutated to inhibit splicing or 3′ end processing. Importantly, we provide evidence that many endogenous pre-mRNAs are also co-transcriptionally degraded by Xrn2 when their processing is inhibited by Spliceostatin A. Our data therefore establish a previously unknown function for Xrn2 and an important further aspect of pre-mRNA metabolism that occurs co-transcriptionally.